EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION DAN TALKING STICK TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI ASPEK PSIKOMOTORIK PADA SISWA KELAS VIII MTsN KARANGMOJO I MAGETAN TAHUN AJARAN 2010/2011 - Maharani, Swasti (JIPM, 2012)
The aims of this research are : 1) To find out which is more effective, Group Investigation or Talking Stick learning on the mathematics achievement of the students of MTSN Karangmojo I Magetan. 2) To find out is there any differences of the mathematics achievement on Group Investigation and Talking Stick learning from the studentâs psychomotoric aspect. This research was conducted from March 2011 to June 2011, using experiment method. The population is all of students of grade VIII MTsN Karangmojo I Magetan. The sample is assigned to two out of all classes, those are : VIII A as control class and VIII B as experiment class. The data were collected using test and observation. It was analyzed using two ways anova. The result of this research are : 1) Group Investigation learning is more effective than Talking Stick learning. 2) There are the difference of the mathematics achievement on Group Investigation and Talking Stick learning from the studentâs psychomotoric aspect.Key Words : Group Investigation and Talking Stick learning, the mathematics achievement and studentâs psychomotoric aspect.